Exploration in Strategic Planning - Irina V. SHARF; Natalia V. CHUKHAREVA; Anna V. ANTOSHKINA (Communications of International Proceedings, 2020)
The perspectives of resource-producing regions are closely connected with the state of mineral resource base, which at present is deteriorating qualitatively and quantitatively, hence, in many strategic programs of socio-economic development particular attention is paid to the increase of exploration activities, development of the Earth sciences to expand the knowledge on poorly studied areas based on latest technologies and innovation. The article presents a comparative analysis of socio-economic aspect of exploration in strategic programs of the chosen countries, namely, Canada, Australia, and Russia, to reveal similarities and differences. The research has shown various approaches toward development of new areas and practices of stimulating exploration activities as well as similarities in socio-economic consequences of field prospecting, exploration, and development.
Keywords: Mineral resource; strategic planning; stimulation of exploration; region; socio-economic development.